Adoption of online banking features by financial intermediaries. (27th December 2012) - Zhang, Yu; Chen, Kuo Lane; Lee, Huei; Yang, Jiaqin
This paper investigates how the size and type of financial intermediaries affect the adoption of online banking features. One hundred and ten commercial banks, savings banks and credit unions of different sizes, and state coverage were studied. Service feature ranges from basic services such as checking and savings accounts to financial shopping mall service such as comprehensive one–for–all account. Security feature includes: password, encryption, security questions, limited to registered computers, and a banner or icon to certify the website. Our survey results show that comparing to savings banks and credit unions, commercial banks with larger size, and greater state coverage tend to offer more online service features. However, there is no significant difference between commercial banks and credit unions in online security methods. This is due to the fact that most local credit unions do not maintain online banking interface themselves, but delegate a third party for secure online services.